Opportunities and challenges of indigenous biotic weather forecasting among the Borena herders of southern Ethiopia - Ayal, Desalegn Y.; Desta, S.; Gebru, G.; Kinyangi, James; Recha, John W.M.; Radeny, Maren A.O. (Springer, 2015)
The practical utilization of available modern as well as traditional weather forecasting systems builds herders’ resiliency capacity to climatic shocks. The precision and reliability of the forecasting system determines its creditability and acceptance by the users to be proactive in the decisions they make based on the forecasted information. It has been postulated that traditional weather forecasting systems are becoming less reliable due to repeated faulty forecasts. The study assesses the current status of the Borana traditional weather forecasting system and how traditional experts make weather forecasts based on biotic indicators such as intestinal readings, changes in plant and animal body languages. Questionnaire survey, field observations, focus group discussions and interviews with relevant key informants were employed to obtain data. Collected field data was compared with National Metrological Service Agency instrumental data for consistency. Results reveal that herders made short term weather forecasts using intestinal readings, and observed changes in plant and animal body languages. The study shows the extent how public confidence in the accuracy of indigenous weather forecasting skills has been gradually eroded overtime due to faulty forecasts. The precision and credibility of the traditional weather forecast steadily declined and led to repeated faulty predictions. Poor documentation, oral based knowledge transfer system, influence of religion and modern education, aging and extinction of traditional experts were identified as the major causes undermining the vitality of traditional climate forecast. Traditional weather foresting knowledge and skill could have some utility and also serve as a starting point to scientifically study the relationship between various signs and implied climatic events. This article recommends before traditional Borana weather forecasting system completely disappears, a remedial action should be carried out to rescue this long established wisdom, knowledge and skill and maximize the benefits from what works well. The forecast needs of herders could be rendered by a combination of modern and traditional weather forecasting services. Further research is required to explore possible area of complementarity between the modern and traditional forecasting systems for improved efficiency and effectiveness in predictability, dissemination and advice.